FORMULATIONS AND PHYSICAL STABILITY TEST OF OLIVE OIL (Olea europaea L.) LIP BALM WITH ILLIPE BUTTER - Rise Desnita; Desy Siska Anastasia; Mutiara Dinda Putri (Universitas Muhammadiyah Magelang, 2022)
Lip balm is a preparation that is applied on the lips to protect the lips from damage. Olive oil is an oil that has emollient properties that are able to maintain moisture, flexibility, and smoothness in the skin. Oleic acid content in olive oil has the ability to improve skin permeability. Tengkawang fat is known to have characteristics similar to cocoa fat so it is used as a base. This study will provide an overview of the physical properties of olive oil lip balm (olive oil) with tengkawang fat based on storage for 28 days. Lip balm preparations are made in three concentration variations for 10%, 15%, and 20%, Then the preparation will be observed organoleptically changes, homogeneity of the preparation, pH and temperature of the melting point. The results ANOVA test of pH showed there was no significant difference between storage time to pH for each formula. Organoleptic and homogeneity test show good results in the absence of discoloration, odor, and texture and homogeneity during the storage period. The evaluation of lip balm preparations for each formula showed that the preparations were physically stable during the 28-day storage period.